Microbial Flora Changes in Cesarean Section Uterus and Its Possible Correlation With Inflammation - Yang, Xing; Pan, Xinyi; Cai, Meihong; Zhang, Bolun; Liang, Xiaoyan; Liu, Guihua (Frontiers in Medicine, 2021)
Background: It has not been fully elucidated whether the change of the uterus flora is correlated to the impaired fecundity. This case-control study aimed to analyze the differences in uterus microbial flora between women with post-cesarean section scar diverticulum (CS group) and women after vaginal delivery (control group), exploring the correlation between differentially expressed microbial flora and inflammation. Methods: Infertile women underwent hysteroscopy were enrolled in this case-control study. The swab samples were classified as four subgroups: CS cervix group, CS endometrium group, control cervix group, and control endometrium group. The total DNA obtained from 16 women (a total of 31 samples, the cervix or endometrium) was extracted for 16S rDNA analysis. The Luminex platform was used to detect the abundance of 34 kinds of local inflammatory cytokines in 32 endometrium samples, and the correlation between microbial flora and inflammatory cytokines was analyzed. Results: The alpha and beta diversity analysis indicated that the microbial diversity was higher in the CS group compared to the control group, especially in endometrium tissues. The heatmaps revealed that the microbial flora structure differs at each level of phylum-class-order-family-genus among groups. The analysis of four of the most prominently changed microbial flora revealed that Lactobacillus in the cervix was significantly higher in the control group, when compared to the cesarean section group (P<0.05). Furthermore, Proteobacteria and Neisseriaceae had a higher abundance in the CS groups, especially in cervical tissue (P<0.05), while Staphylococcaceae increased only in CS endometrium tissue (P<0.05). Next, these women were re-divided into the high-Staphylococcaceae group and low-Staphylococcaceae group, and the abundance of 34 kinds of local inflammation cytokines was compared between groups. It was found that there was a positive correlation between Staphylococcaceae and IL-2, and a negative correlation between Staphylococcaceae and IL-8 (P<0.05). Conclusion: These present results suggest that the disrupted uterus microbiota composition in women with CS may closely associated with local inflammatory. The interplay between the microbiota and immune system may be linked to clinical disorders, the potential mechanisms require further exploration.